Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.